THE TEACHERS' CLINIC. - Carson, A. B.; Simons, Harry; Singer, Frank A.; Stevens, Robert G. (The Accounting Review, 1956)
Abstract In the area of consolidated statements, as perhaps in no other, there is the danger that the student will place full reliance upon working papers, elimination patterns, and technical procedures as demonstrated in the classroom and textbook in achieving a set of answers. If the student simply applies mechanical techniques, without thinking of the consolidation framework set by the past or the frame-work to be provided for the future, he will be unable to offer any theoretical support for his conclusions and will not possess any real confidence in them. Even worse, if the student leaves the matter at this stage, be may feel that certain areas in accounting are beyond his grasp, and may thus develop a basic insecurity. The possibility of any such insecurity can be avoided by the careful presentation of this subject matter.